Antibacterial Activity of Ecoenzyme from Garut Orange Peel (Citrus nobilis var.chrysocarpha) against Propionibacterium acne - Nurani Ai Erlinawati, Nurani Ai Erlinawati; Mamay, Mamay; Yogi Rahman Nugraha, Yogi Rahman Nugraha (Karsa Husada Health Institute Garut, 2025)
Acne is a skin disorder that often occurs in adolescents. Propionibacterium acnes is a bacteria that causes acne. The use of antibacterial substances is very important to prevent and control this bacterial infection. One of the advances in the use of antibacterials comes from the use of ecoenzyme. The process of managing organic waste with ecoenzyme can be an effective and environmentally friendly waste management strategy. Garut orange with the scientific name Citrus nobilis var. chrysocarpa is a local wisdom fruit. Orange peel which is a waste that increases in quantity when the harvest season arrives can be used in the manufacture of ecoenzyme. This study aims to evaluate the antibacterial ability of ecoenzyme from garut orange peel against Propionibacterium acnes bacteria. The fermentation time for ecoenzyme production varied from 30, 60 and 90 days.. The method for the eco enzyme antibacterial test uses the disc diffusion method. Three variations in eco enzyme concentration used to inhibit the growth of isolated bacteria are 33%, 66% and 100%. Ecoenzyme from Garut orange peel shows antibacterial activity against Propionibacterium acne. Antibacterial activity shows an increase with increasing fermentation time of ecoenzyme